Disease Perception and Preventive Behavior: The Vaccination Response to Local Measles Outbreaks - Sarah Hofmann (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2022)
This paper examines the role of perceived disease risk for vaccination behavior. Using health insurance claims data, I estimate the effect of local measles outbreaks in Germany on first and second dose measles vaccinations in children as well as catch-up vaccinations in adults. In my empirical strategy, I exploit the variation in timing and location of regional disease outbreaks and estimate a two-way fixed effects model with birth cohort and region fixed effects. Basic underlying assumption is that measles outbreaks alter perceptions regarding the disease risk. The robustness of this approach with regard to possible bias due to heterogeneous treatment effects under differential treatment timing is assessed through the use of alternative estimators. The results show that measles outbreaks within a region increase the share of children who receive their vaccination on time by 0.8 percentage points for both the first and second vaccination. This corresponds to a reduction in the share of not timely vaccinated children of about 4.1% and 2.6% for the first and second dose, respectively. They further also increase the rate of monthly catch-up vaccinations in adults by about 15% for the age group 20-30 to up to 46% for those at ages 40-50 in the first six months after an outbreak. One important finding is that regional outbreaks do not lead to increases in vaccinations in other regions even if public attention extends beyond the affected region. This suggests that behavioral responses are driven by affective rather than deliberative risk perception. Also, vaccination effects can be observed only in the few months following the outbreak, which indicates that changes in the perceived disease risk due to a local measles outbreak are short-lived and fade away quickly once the disease outbreak is over.
Keywords: I12; I18; C21; 330; Vaccinations; Immunizations; Measles; Public Health